High-rate pacing suppresses Torsade de Pointes arrhythmias and reduces spatial dispersion of repolarization in the chronic AV-block dog model - Loen, Vera; Van Weperen, Valerie Y. H.; Beekman, Henriëtte D. M.; Van Bavel, Joanne J. A.; Meijborg, Veronique M. F.; Van der Waal, Jeanne G.; Coronel, Ruben; van der Heyden, Marcel A. G.; Vos, Marc A. (Frontiers in Physiology, 2023)
Background: An electrical storm of Torsade de Pointes arrhythmias (TdP) can be reproducibly induced in the anesthetized chronic AV-block (CAVB) dog by infusion of the IKr-blocker dofetilide. Earlier studies showed that these arrhythmias 1) arise from locations with high spatial dispersion in repolarization (SDR) and 2) can be suppressed by high-rate pacing. We examined whether suppression of TdP by high-rate pacing is established through a decrease in SDR in the CAVB dog.Methods: Dofetilide (25 µg/kg in 5 min) was administered to 5 anesthetized CAVB dogs to induce TdP arrhythmias. During the experiments, animals were continuously paced from the right ventricular apex at 50 beats/minute (RVA50). Upon TdP occurrence and conversion, RVA pacing was consecutively set to 100, 80 and 60 beats/minute for 2 minutes, referred to as pacing blocks. To determine the additional anti-arrhythmic effects of HRP over defibrillation alone, the number of arrhythmic events and SDR at RVA100 were compared to data from three previously conducted experiments, in which dogs underwent the same experimental protocol but were paced at RVA60 upon TdP occurrence (RVA60retro). In all experiments, recordings included surface electrocardiogram and mapping by 56 intramural needles, each recording four electrograms, evenly inserted into the ventricular walls and septum. For each pacing block, the number of ectopic beats (EB), and TdP severity were scored. SDR was quantified as the average difference in repolarization time within four squared needles (SDRcubic).In 4 out of 5 animals, pacing at RVA100 suppressed TdP occurrence. One dog could not be converted by defibrillation after the initial TdP. Compared to RVA50, pacing at RVA100, but not RVA80 and RVA60, significantly reduced the TdP score (78±33 vs 0±0, p<0.05 and vs 12.5±25 and 25±50, both p>0.05). The reduction in TdP score was reflected by a significant decrease in SDRcubic (125±46 ms before TdP vs 49±18 ms during RVA100, p<0.05), and SDR was smaller than in the RVA60retro animals (101±52 ms, p<0.05 vs RVA100).In CAVB dogs, high-rate pacing effectively suppresses TdP, which, at least in part, results from a spatial homogenization of cardiac repolarization, as reflected by a decrease in SDR.